Cóntrolled Therapeutic Evisceration - Torterolo, Edgardo; Viñuela, Enrique; Perrier, José P; Piñeyro, Alberto; Bergalli, Luis; Peyroulou, Alfredo (Cirugía del Uruguay, 1981)
Control1ed therapeutic evisceration is a procedure which consists in placing a substitute tissue instead of closing the abdominal wal! in cases of successive reoperations, hyperseptic peritonitis, evisceration in seriously sick patients or in cases of ample resections due to superficial infections.